Understanding Electric Vehicle Adoption in Türkiye: Analyzing User Motivations Through the Technology Acceptance Model - Bektas, Baris Can; Alcura, Guezin Akyildiz (MDPI, 2024)
The popularity of electric vehicles offers the opportunity to analyze decision-making processes by examining user behavior. Determining the motivation of the user to use an innovation will guide decision-makers in supporting the innovation in question. This study investigates the factors electric car users in T & uuml;rkiye consider based on the Technology Acceptance Model. A questionnaire was used to measure Perceived Ease of Use, Perceived Usefulness, and Intention to Use with the external factors of Subjective Norm, Compatibility, and Image. The relationships were analyzed with PLS-SEM established with the participation of 414 electric vehicle users. Subjective Norms and Image directly impact Perceived Usefulness, Perceived Ease of Use, and Intention to Use. It has been determined that Compatibility has a direct effect on Ease of Use and an indirect effect on Usefulness and Intention. According to this study, in which most people are dissatisfied with charging and range issues, the opinion of the social environment and family is the most important external factor affecting intention. Our findings suggest improving the charging station network and technology, as well as implementing informative activities related to the features of electric vehicles, in order to contribute to users' adoption of electric vehicles.
Keywords: electric cars; technology acceptance model; image; subjective norm; compatibility; PLS-SEM; PURCHASING INTENTIONS; CONSUMER ATTITUDES; VALIDITY; SERVICES; Science & Technology - Other Topics; Environmental Sciences & Ecology